Low temperature conditioning of garlic (Allium sativum L.) “seed” cloves induces alterations in sprouts proteome - Dufoo-Hurtado, Miguel D.; Huerta-Ocampo, José Á.; Barrera-Pacheco, Alberto; Barba de la Rosa, Ana P.; Mercado-Silva, Edmundo M. (Frontiers in Plant Science, 2015)
Low-temperature conditioning of garlic “seed” cloves substitutes the initial climatic requirements of the crop and accelerates the cycle. We have reported that “seed” bulbs from ‘Coreano’ variety conditioned at 5 °C for five weeks reduces growth and plant weight as well as the crop yields and increases the synthesis of phenolic compounds and anthocyanins. Therefore, this treatment suggests a cold stress. Plant acclimation to stress is associated with deep changes in proteome composition. Since proteins are directly involved in plant stress response, proteomics studies can significantly contribute to unravel the possible relationships between protein abundance and plant stress acclimation. The aim of this work was to study the changes in the protein profiles of garlic “seed” cloves subjected to conditioning at low-temperature using proteomics approach. Two sets of garlic bulbs were used, one set was stored at room temperature (23 °C), and the other was conditioned at low temperature (5 °C) for five weeks. Total soluble proteins were extracted from sprouts of cloves and separated by two-dimensional gel electrophoresis. Protein spots showing statistically significant changes in abundance were analyzed by LC-ESI-MS/MS and identified by database search analysis using the Mascot search engine. The results revealed that low-temperature conditioning of garlic “seed” cloves causes alterations in the accumulation of proteins involved in different physiological processes such as cellular growth, antioxidative/oxidative state, macromolecules transport, protein folding and transcription regulation process. The metabolic pathways affected include protein biosynthesis and quality control system, photosynthesis, photorespiration, energy production, and carbohydrate and nucleotide metabolism. These processes can work cooperatively to establish a new cellular homeostasis that might be related with the physiological and biochemical changes observed in previous studies.